Evaluation of Education Building Based on Healthy Building Aspects (Air Circulation, Humidity, Natural Light Intensity) - Landrian, Lutfi; Maulina, Wilda; Nyssa, Amelia Rizyan (Universitas Muhammadiyah Surakarta, 2025)
This study aims to evaluate the condition of building quality by using the main principles of healthy buildings. The main principles of a Healthy building should be in good condition in three aspects, there are air circulation (air velocity and air temperature), humidity, and natural light intensity. The evaluation was conducted at Mochtar Riady Plaza Quantum (MRPQ), one of the Laboratory buildings at the Universitas Indonesia, Depok, Indonesia. The process is carried out by first analyzing the existing condition of the building and evaluating it with the standard of comfort in Standar Nasional Indonesia (SNI). Then it will be determined which parts need to be improved and continued with the intervention using simulation software Dialux, Ansys, and Revit. It was found that this building had shortcomings in all three aspects of the healthy building, such as humidity levels above the standard 40-60%, lack of natural air velocity for air circulation, high air temperature, and low natural light intensity in corridors and auditoriums. The results of interventions in all three aspects of health could increase by 66.5% in air velocity for air circulation, reduce 13.3% in humidity, and increase by 78.2% in natural light intensity aspects.